Legal Aspects of Business Competition in the Procurement of Covid-19 Vaccine by Bio Farma Ltd - Tri Utomo Wiganarto; Asenar Asenar; Elisatris Gultom (Kanun Jurnal Ilmu Hukum, 2021)
The purpose of this research is to analyze the exclusion of monopoly by State Owned Enterprises (BUMN) based on the provisions of business competition law in the procurement of the Covid-19 vaccine by Bio Farma (Persero) Ltd. Indonesia is being hit by the Covid-19 outbreak. This condition has had a negative impact in various fields. To overcome this, one of the government's efforts is to bring in vaccines to prevent the spread, and the procurement of vaccines is given to Bio Farma Ltd. There are indications of monopoly actions in the procurement of Covid-19 vaccines by Bio Farma Ltd. This research uses the approach statute approach and conceptual approach. The technique of tracing legal materials uses field study techniques and document studies (library research), as well as study analysis is using qualitative analysis. The results of the research and the discus-sion show that the procurement process for the Covid-19 vaccine is strictly regulated by the government. Even the quantity, procurement, and distribution are coordinated by the government in this case through the assignment of SOEs (BUMN) as regulated in Presidential Regulation Number 99 of 2020 as amended by Presidential Regulation Number 14 of 2021. The results of the study show that the actions taken by SOEs (BUMN) in this case Bio Farma (Persero) Ltd in procuring the Covid-19 vaccine is included in the excluded monopoly category, because it meets the elements of the provisions in Article 50 paragraph a. Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.